FORMULATION AND EVALUATION OF IBRUTINIB NANOSPONGES INCOPORATED TABLET - VISWAJA, MEDIPALLI; BHIKSHAPATHI, D. V. R. N.; PALANATI, MAMATHA; BABU, A. KISHORE; GOJE, ARJUN (International Journal of Applied Pharmaceutics, 2023)
Objective: The present investigation was undertaken to prepare polymeric nanosponges of an anti-cancer drug, ibrutinib to achieve controlled and improved drug release. Methods: Nanosponges using a polymer (ethyl cellulose, poloxamer 188 and eudragit RL 30 D) and polyvinyl alcohol as a cross-linker were prepared successfully by the emulsion solvent evaporation method. Prepared nanosponges were evaluated for particle size, zeta potential, entrapment efficiency and in vitro drug release. Nanosponges with good drug release were formulated into tablets and evaluated for miromeritic properties, post-compression parameters and in vitro release and the final optimised formulation was characterized for globule size, zeta-potential, FTIR, SEM and stability studies. Results: The nanosponges' particle sizes were discovered to range between 86.31 nm and 162.4 nm, the Zeta Potential ranges from-22.1 to-29. It was discovered that the drug entrapment efficiency ranged from 92.21 to 99.23% and Formulation F18 exhibited the highest drug release rate of 99.73% in 12h and was discovered to demonstrate good, satisfying results. The tablet formulation's micromeritic and post-compression parameters were examined, and it was discovered that F18 had good flow qualities. F18 had a mean globule size of 133.6 nm, a zeta potential of-22.1 mV, and SEM images revealed a sphere-like structure. The complexation of ibrutinib and the amorphous condition of the medication and formulation were confirmed by the FT-IR, and stability investigations to be stable for three months. Conclusion: Hence, Ibrutinib loading into nanosponges made using the emulsion solvent evaporation process thus successfully boosted and controlled the drug release.